Association between coffee and caffeine consumption and chronic kidney disease - Panpan Gao; Xinrong Ji; Weiwei Wang; Yao Chen; Zhan Gao; Zengli Yu (Scientific Reports)
Abstract Chronic kidney disease (CKD) is a significant global health issue associated with cardiovascular complications. While coffee, tea, and caffeine consumption have been linked to various health benefits, their relationship with CKD remains unclear. We conducted a cross-sectional analysis of NHANES 1999–2018 data, including 49,827 participants, assessing dietary intake through two 24-hour recalls and determining CKD status via the CKD-EPI equation. Our results showed that after adjusting for covariates, higher coffee consumption (> 352.5 g/day) was associated with lower odds of CKD (OR 0.760, 95% CI 0.701–0.823), as was tea consumption (OR 0.913, 95% CI 0.843–0.89). The highest tertile of caffeine consumption also showed a significantly reduced odds of CKD (OR 0.734, 95% CI 0.674–0.799). These findings suggest that coffee, tea, and caffeine consumption may be associated with better renal function, highlighting potential dietary strategies for CKD prevention.